ATMPH 2020
DOI: 10.36295/asro.2020.231627
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Extracted Teeth According to the Site, Type, Age, and Sex: A Retrospective Single-Center Study from Baghdad, Iraq

Abstract: Background: Teeth extraction is a common therapeutic practice in dentistry. Clinics for management a variety of pathological, traumatic, or congenital conditions. The prevalence of teeth extraction is related to the dental hygiene of the participants. Aim: This study aimed to demonstrate the distribution of the site and type of extracted teeth according to the age and sex of the participants. Methods: This retrospective study was conducted in teaching dentistry clinics in the Al-Rafidain College University thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This age group seems to have more dental extractions compared to other age groups. In their study on Iraqi patients' sample, Salih & Al-Nimer found that the highest percentage of tooth extraction (26.96%) was recorded in this age group (13) It is generally agreed that posterior teeth loss in both upper and lower arches is more common than upper and lower anterior teeth loss (13,14) . This certainly influences the demand for a dental implant in different jaw regions for both gender groups.…”
Section: Meerp Ltdmentioning
confidence: 96%
“…This age group seems to have more dental extractions compared to other age groups. In their study on Iraqi patients' sample, Salih & Al-Nimer found that the highest percentage of tooth extraction (26.96%) was recorded in this age group (13) It is generally agreed that posterior teeth loss in both upper and lower arches is more common than upper and lower anterior teeth loss (13,14) . This certainly influences the demand for a dental implant in different jaw regions for both gender groups.…”
Section: Meerp Ltdmentioning
confidence: 96%